PENGEMBANGAN PETUNJUK PRAKTIKUM IPA BERBASIS KETERAMPILAN PROSES UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Yuanita Yuanita; Fitha Yuniarita (Universitas Muhammadiyah Surakarta, 2018)
This study aims to develop science practices instruction based on science critical thinking skill and tomeasure the effectiveness of the product toward critical thinking skill of elementary students in Gerunggang. The type of this research is research and development. The research instruments were documentation, expert sheet validation, observation sheet, feasibility sheet, and the test instrument of students’ critical thinking. The subjects of this study were elementary school students in Gerunggang. The data subjects in this study were elementary school students and teachers in higher class. Based on the results of the development using the steps from Timpuslitjaknov, which include: (1) needs analysis, (2) initial product development, (3) expert validation and revision, (4) smaller-scale field trials, and (5) larger-scale field trials. Depelopment study of science with the results of the feasibility test by 3 expert (media, material, and language) the results are very feasible, smaller-scale tests and larger-scale results with decent results. The effectiveness results of critical thinking skills are: 1) indicators provide simple explanations with N-Gain 0.40 medium category, 2) complete indicators with N-Gain 0.37 Medium category, 3) Indicators provide explanations with N-Gain 0.28 low category, so, it can easily be concluded that the result development of science practical instruction based on science critical thinking skill can enhance studnets’ critical thinking skill for elementary school students.